Effect of Pro.Sol, Folicist and Cultivar on Leaf Nutrients of Olive (Olea europaeaL.) Transplants - Saeed, Gulala M. A.; Mayi, Azad A. (Sulaimani Journal for Pure and Applied Sciences, 2016)
This study was carried out during the growing season (2014) at Bakrajo Nursery Station/ Sulaimani, Kurdistan Region-Iraq. Two years old, uniform and healthySorani and Picual olive cultivars transplants were grown in 5 kg pots filled with soil in order to investigate the effect of three concentrations of Pro.Sol (0,100 and 200) and three Folicist concentrations (0, 60 and 120) as well as their interactions on leaf mineral contents of the two olive cultivar transplants. The results showed that 120 folicist significantly affected the leaf (N, K, Ca and Fe), while 60 significantly affected the leaf P content. However, 100 Pro.Sol affected significantly leaf (N, P and Fe), whereas 200 affected leaf (N,K and Ca) contents. However, Sorani cultivar was superior significantly to the Picual with regard to (N, K and Fe) leaf contents while the last cultivar was superior significantly to the first with respect to (P and Ca) contents.
Keywords: ProSol; Folicist; Olivecultivar; leaf nutrient